2014
DOI: 10.1002/embr.201337945
|View full text |Cite|
|
Sign up to set email alerts
|

Toll‐like receptor 9 protects non‐immune cells from stress by modulating mitochondrial ATP synthesis through the inhibition of SERCA 2

Abstract: Toll-like receptor 9 (TLR9) has a key role in the recognition of pathogen DNA in the context of infection and cellular DNA that is released from damaged cells. Pro-inflammatory TLR9 signalling pathways in immune cells have been well investigated, but we have recently discovered an alternative pathway in which TLR9 temporarily reduces energy substrates to induce cellular protection from stress in cardiomyocytes and neurons. However, the mechanism by which TLR9 stimulation reduces energy substrates remained unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…Activation of cardiac inflammatory nodes, specifically TLR9, influences mitochondrial cal- cium by inhibition of SERCA2, reducing mitochondrial calcium uptake and ATP synthesis (40). This has been interpreted as a stress protection response in cardiomyocytes but might also be detrimental when activated long-term, leading to functional ATP deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of cardiac inflammatory nodes, specifically TLR9, influences mitochondrial cal- cium by inhibition of SERCA2, reducing mitochondrial calcium uptake and ATP synthesis (40). This has been interpreted as a stress protection response in cardiomyocytes but might also be detrimental when activated long-term, leading to functional ATP deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 21 signals are crucial for the control of a broad range of cellular functions. 20,21 Upon TLR stimulation, intracellular calcium levels are increased, [34][35][36][37][38][39] either from internal stores in the ER lumen or from influx from the extracellular space. Previous studies have suggested that increased intracellular calcium plays important roles in mediating the TLR-triggered immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that increased intracellular calcium plays important roles in mediating the TLR-triggered immune response. [35][36][37][38][39][40][41][42][43][44][45][46][47] In most studies, attention has been paid to intracellular calcium mobilization. However, TLRs may trigger calcium release from the ER and then STIM-ORAImediated calcium entry.…”
Section: Discussionmentioning
confidence: 99%
“…FRET-based measurement of mitochondrial ATP concentration in cardiomyocytes was measured as previously described (8,33). Briefly, FRET signal was measured in cardiomyocytes infected with adenovirus encoding mit-AT1.03 with an Olympus IX-81 inverted fluorescence microscope (Olympus) using a PL APO 60×, 1.35 N.A., oil immersion objective lens (Olympus).…”
Section: Methodsmentioning
confidence: 99%